8 Multi-disciplinary leadership and the impact on education for children with medical needs. (22nd November 2019) - Franklin, Jayne; Marks, Stephen; Begent, Joanna; Goldsmith, Jackie
Abstract : Introduction: Continuing education should be an integral element in GOSH's support for children to enable them to reach their life goals and to fulfill their potential. Research by Public Health England identifies that education is one of the key social determinants of future health and yet national legislative and statutory duties around education are not always embedded within NHS settings or addressed as part of the child's wider health outcomes. Section 19 of Education Act clearly states that there must be suitable full-time education, for children who, because of illness, would otherwise not receive suitable education. This must allow them to take appropriate qualifications, prevent them from slipping behind their peers and allow them to reintegrate back into school as soon as possible. Methods: Retrospective review of GOSH school staff team and teaching sessions Results: The School team has grown by 50% since 2011 with teaching achieved in over 17, 000 sessions. This growth is not only in response to increasing complex inpatient admissions but due to a growing mutual understanding through improved MDT practice and expert partnerships. Conclusions: The key factors influencing effective partnerships with health professionals, hospital schools, AHPs and the child's mainstream schools. It is this approach, which transforms a child's educational outlook, holistic outcomes and influences their long-term health outlook. Chronic health conditions which lead to significant absences from school are highly likely to have a serious emotional impact and can lead to children experiencing loneliness. One parent recently described the dramatically isolating impact that three years of exclusion due to acute leukemia had had on her son. Once a socially confident child, he now suffers from anxiety and OCD he has lost his confidence in relating to other children.